Nilai Pendidikan Karakter dalam Novel Kembara Rindu Karya Habiburrahman El Shyrazi - Cendani, Tinezia; Effendi, M. Syahrun (Silampari Bisa: Jurnal Penelitian Pendidikan Bahasa Indonesia, Daerah, dan Asing, 2022)
This study aims to describe the value of character education in the novel Kembara Rindu by Habiburrahman El Shirazy. The method used is a qualitative method. The data collection technique used is the documentation technique. The data analysis technique is by describing the entire contents of the novel, marking the value of character education, interpreting, and drawing conclusions. Test the validity of the data by checking and expert validity. From the results of the study, there are 5 types of character education values ​​and the dominant ones used in the novel Kembara Rindu by Habiburrahman El Shirazy are the values ​​of character education related to oneself as much as 52.47%, then the value of character education related to relationships with fellow creatures is 25, 31%, then the value of character education related to God Almighty (religious) 20.37%, and the value of character education related to nationality as much as 1.23%, and finally the value of character education related to the environment as much as 0.62% . The value of character education shown in this novel is more about how the relationship between creatures. Therefore, from the results of this study, it should be noted how the value of character education should be implemented in schools.